2023
DOI: 10.1021/jacs.3c03938
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Crystalline Nitrone-Linked Covalent Organic Frameworks Via Kröhnke Oxidation

Abstract: Developing diverse synthetic routes to prepare various crystalline covalent organic frameworks (COFs) and enrich the family of COFs is very important and highly desirable. In this research, we demonstrate that Kröhnke oxidation (originally developed to prepare carbonyl compounds) can be employed as an efficient method to construct two crystalline nitrone-linked COFs (CityU-1 and CityU-2) through the ingenious design of the polynitroso-containing precursors as well as the exquisite control of the polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 77 publications
0
31
0
Order By: Relevance
“…Chemie C=N, respectively (Figure 1b). [41] Upon oxidation by m-CPBA, due to the decreased electron density of nitrogen atoms, the C 1s XPS peak arising from C=N + in NQÀ COF E5 À O is upshifted to a higher binding energy of 288.6 eV. This is the same case for N 1s XPS spectrum, where a noticeable upshift of binding energy from 399.2 eV to 400.3 eV is also observed after oxidation (Figure 1c).…”
Section: Methodsmentioning
confidence: 60%
“…Chemie C=N, respectively (Figure 1b). [41] Upon oxidation by m-CPBA, due to the decreased electron density of nitrogen atoms, the C 1s XPS peak arising from C=N + in NQÀ COF E5 À O is upshifted to a higher binding energy of 288.6 eV. This is the same case for N 1s XPS spectrum, where a noticeable upshift of binding energy from 399.2 eV to 400.3 eV is also observed after oxidation (Figure 1c).…”
Section: Methodsmentioning
confidence: 60%
“…Covalent organic frameworks (COFs) possess many desirable features such as robust structures, large surface areas, and well-defined pore environments for potential applications in gas separation, conductivity, drug delivery, and catalysis. As interlayer π–π interactions provide an important driving force for COF synthesis, most COFs have two-dimensional (2D) structures with sp 2 carbon linkages and exhibit rapid exciton diffusion to quench excited states. …”
mentioning
confidence: 99%
“…In this regard, porous coordination polymers such as metal-organic frameworks (MOFs) and covalent-organic frameworks (COFs) have shown great promise as multifunctional, designer materials that can combine several unrivaled physical properties in one material system. 1,[10][11][12][13][14][15][16][17] For example, Evans et al 1 have recently demonstrated Fig. 1 Comparison of thermal conductivity as a function of elastic modulus for a wide range of materials at room temperature.…”
mentioning
confidence: 99%
“…In this regard, porous coordination polymers such as metal–organic frameworks (MOFs) and covalent-organic frameworks (COFs) have shown great promise as multifunctional, designer materials that can combine several unrivaled physical properties in one material system. 1,10–17 For example, Evans et al 1 have recently demonstrated that boronate ester-linked 2D COF thin films are endowed with low dielectric constants and possess a room temperature thermal conductivity of ∼1 W m −1 K −1 (Fig. 1) along the laminar pores, marking a new paradigm in materials design that combines relatively high thermal conductivity with low mass density.…”
mentioning
confidence: 99%